Apixaban: new anticoagulant for stroke prevention. Issue 11 (18th June 2013) - Chaplin, Steve; Manning, Lisa; Lam, Man Yee; Robinson, Thompson
Abstract Apixaban is a new oral anticoagulant licensed for the prevention of stroke and systemic embolism. In our New products review, Steve Chaplin presents the clinical data relating to its efficacy and adverse events compared with warfarin and aspirin, and hospital specialists discuss its place in stroke prevention.